Banjar Mantras as a Medium for the Preservation of Cultural and Religious Values in South Kalimantan - Ida Komalasari; Afdhal Kusumanegara; Noor Leha; Ida Rusdiana; Muhammad Rizki Roli Novian (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Banjar mantras are a form of oral literature that represents the knowledge, beliefs, and values of the Banjar community transmitted across generations. This study aims to describe the forms, cultural values, and religious values of Banjar mantras as a means of cultural preservation in Batang Kulur Kiri Village, Hulu Sungai Selatan Regency. This qualitative study employed a descriptive method. The data consisted of Banjar mantra utterances and information concerning their use and transmission, obtained from community members with knowledge and experience of Banjar mantras. Data were collected through observation, interviews, and documentation and analyzed through data collection, reduction, presentation, and conclusion drawing. The findings reveal various forms of Banjar mantras based on their functions, including healing, self-protection, love and attraction, travel safety, and childbirth. These findings demonstrate that Banjar mantras embody cultural, educational, and religious values that represent Banjar cultural identity and warrant documentation and preservation as cultural heritage.